Hubungan Kualitas Pelayanan Keperawatan dengan Kepuasan Pasien di Ruangan Rawat Inap Rumah Sakit UMMI Bogor Tahun 2025 - Mayang Kusnadi; Solehudin Solehudin; Inas Syabanasyah (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Nursing services are a fundamental part of the hospital service system because nurses interact frequently with patients, particularly in inpatient rooms. The quality of nursing services significantly impacts patient satisfaction. This study aims to determine the relationship between the quality of nursing services and patient satisfaction in the inpatient rooms of UMMI Hospital Bogor. This study used a correlational analytical research design with a cross-sectional approach. The population in the study were 1,944 inpatients at UMMI Hospital Bogor. The sample calculation used the Slovin formula with a simple random sampling technique and obtained 332 respondents. The research instrument for the quality of nursing services was based on the five dimensions of SERVQUAL (tangible, reliability, responsiveness, assurance, and empathy) and a patient satisfaction questionnaire. Data analysis was performed univariately and bivariately using the Chi-Square Test statistic. The results showed that the majority of respondents rated the quality of nursing services as good, namely 214 people (64.5%), while respondents who rated the quality of nursing services as poor were 118 people (35.5%). Patient satisfaction results revealed that of the 332 respondents, the majority (230 people or 69.3%) expressed satisfaction, while 102 (30.7%) expressed dissatisfaction. The statistical test results showed a p-value of 0.000 (p < 0.05). The conclusion of this study is that there is a significant relationship between the quality of nursing services and patient satisfaction in inpatient wards. Therefore, continuous improvement in the quality of nursing services is necessary to enhance patient satisfaction and the quality of hospital services.